ANALISIS AKTIVITAS ANTIOKSIDAN DAN MIKROBIOLOGI PADA FORMULASI MINUMAN FUNGSIONAL SERBUK INSTAN JAHE EMPRIT DAN KAYU SECANG: Analysis Of Antioxidant Activity And Microbiology In Functional Beverage Formulations Of Instant Zingiber Officinale And Sappan Wood Powder - Srimiati, Mia; Syahrial, Sartika Mahardika; Afrizal, Sandra Hakim (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2023)
Emprit ginger (Zingiber officinale var Amarum) has been used as a traditional drink in Southeast Sulawesi. Oleoresin in ginger is an antioxidant because it can prevent the oxidation process by blocking or capturing free radicals. In principle, antioxidants can inhibit the clumping of blood cells, and stimulate the production of nitric oxide (NO) which plays a role in widening blood vessels (vasodilatation) so that it can reduce blood pressure and also inhibit cancer cells. Emprit ginger (Zingiber officinale var Amarum) and secang wood (Caesalpinia sappan L), which have antioxidant properties, will be made into instant functional powder drinks. This research aimed to analyze the content of antioxidant activity, mold, and total clay number (ALT) in the selected formulation, namely the crystallization method (MK2). Organoleptic data (hedonics and hedonic quality) were analyzed using further tests, namely the Mann-Whitney test for significant results. Results of content analysis the selected formulation in powder form contained antioxidant activity of 29895.95 mg/kg, total plate number (ALT) of 1.0 x 102, and mold <10. Meanwhile, in drink form, it contains antioxidant activity of 53335.3 mg/kg, total plate number (ALT) of 1.4 x 102, and mold <10. In conclusion, differences in the manufacturing process also affect the likeability when organoleptically tested by the panelists.